Biographical dictionary of British prime ministers - Eccleshall, Robert; Walker, Graham S. (Routledge, 1998)
The Biographical Dictionary of British Prime Ministers is a wide-ranging, comprehensive guide to the political lives of Britain's prime ministers from Sir Robert Walpole to Tony Blair. Written by some of the leading authorities on British politics this authoritative dictionary provides essential information about each premiership, including facts and analytical debate. Each entry has been written to the same formula and contains: * brief biographical information outlining career history and significant dates and events * a brief summary of the significance and peculiaritie.